At least two high-risk cytogenetic abnormalities indicate the inferior outcomes for newly diagnosed multiple myeloma patients: a real-world study in China. Issue 12 (15th October 2021) - Shen, Man; Yang, Guangzhong; Li, Xin; Geng, Chuanying; Huang, Zhongxia; Chen, Wenming
Abstract: We retrospectively studied the impact of cytogenetic abnormalities in 328 consecutive newly diagnosed multiple myeloma (MM) patients. High-risk cytogenetic abnormalities (HRCAs) included del (17p), amp/gain (1q21), t(4;14), and t(14;16). We defined a standard-risk group by the absence of HRCA, an intermediate-risk group with one HRCA, and a high-risk (HiR) group with at least two HRCAs. The HiR group constituted 14.3% of patients and was associated with a median overall survival (OS) of 28.6 months and progression-free survival (PFS) of 14.0 months. Moreover, the HiR group predicted poor outcomes for OS and PFS in multivariate analyses, and bortezomib prolongation to nine cycles could not bring additional benefit to this entity, suggesting the necessity of more effective therapies for these patients. Furthermore, we confirmed the independent prognostic impact of amp 1q21 in this real-world study.